Genome re-sequencing reveals the evolutionary history of peach fruit edibility - Yang Yu (Nature Portfolio, 2018)
Peach is an economically important fruit crop. Here, the authors carry out a large-scale population genomics analysis of peach, describing its demographic history as well as genes associated with domestication and edibility traits.